IMPROMPTU: A New Interaction Framework for Supporting Collaboration in Multiple Display Environments and its Field Evaluation for Co-located Software Development - Biehl, Jacob T.; Baker, William T.; Bailey, Brain P.; Tan, Desney; Inkpen, Kori; Czerwinski, Mary (Conference on Human Factors in Computing Systems (CHI 2008), 2008)
We present a new interaction framework for collaborating in multiple display environments (MDEs) and report results from a field study investigating its use in an authentic work setting. Our interaction framework, IMPROMPTU, allows users to share task information across displays via off-the shelf applications, to jointly interact with information for focused problem solving and to place information on shared displays for discussion and reflection. Our framework also includes a lightweight interface for performing these and related actions. A three week field study of our framework was conducted in the domain of face-to-face group software development. Results show that teams utilized almost every feature of the framework in support of a wide range of development-related activities. The framework was used most to facilitate opportunistic collaboration involving task information. Teams reported wanting to continue using the framework as they found value in it overall.